Disparities and Female Labor Force Participation - Erlyn Yuniashri; Susilo Susilo; Setyo Tri Wahyudi (AIBPM Publisher, 2022)
Education as human capital will give modern thinking to rural women who consider that women are only terminated to getting married and having children. Investment on education will provide women to engage in decent work in accordance with the SDGs program. However, in Indonesia, there is a gap in facilities and infrastructure between rural and urban area. This study used binary logistic regression analysis due to the dichotomous variables, whether women have the opportunity to work in the informal or formal sector. The data source comes from IFLS-5 with total population 4,952 peoples. The results of the study showed that women from rural areas have the opportunity to work in the informal sector and women with longer education have the opportunity to work in the informal sector.